A case of recurrent flight-induced cerebrospinal fluid shunt overdrainage. (2nd January 2023) - D'Antona, Linda; Craven, Claudia Louise; Haq, Huzaifah; Thorne, Lewis; Matharu, Manjit Singh; Toma, Ahmed Kassem; Watkins, Laurence Dale
Abstract: Shunted patients often complain of headaches after flights. The effect of air travel on shunt systems is unknown. We describe the case of a patient with longstanding hydrocephalus, who suffered flight-induced clinical deterioration and shunt overdrainage in two independent occasions. The patient, clinically stable for 1.5 and 5 years before each episode, reported severe headaches starting during the descent stages of the air travel. On both occasions, brain MRI imaging demonstrated pronounced ventricular size reduction. This case suggests that flight-induced shunt overdrainage can occur and should be suspected in patients with prolonged headaches and/or clinical deterioration triggered by air travel.